The Degree of Study of the Legacy of Ubaydullah ibn Mas’ud Sadr al-Sharia al-Bukhari - Nasrullayev , Nematullo (The Lingua Spectrum, 2025)
This article is devoted to analyzing the degree to which the scientific legacy of Ubaydullah ibn Mas’ud Sadr al-Sharia al-Bukhari (d. 747/1346) has been studied by scholars from the East, Turkey, the West, and Uzbekistan. His works in the fields of Hanafi fiqh, usul al-fiqh, tafsir, logic, kalam, philosophy, Arabic language and rhetoric, history, and fatwas, in particular, important treatises such as "Tanqihul-usul," "Mukhtasarul-Viqaya," and "Fatavai Mawarannahr," occupy an important place in the scientific and spiritual development of Mawarannahr. However, issues such as his personality, the era in which he lived, the method of ijtihad, his place in Sufism, judicial activity, and teaching style have not been sufficiently studied. The article points out the shortcomings of existing research and suggests directions for future scientific research. The research relies on the works of such specialists as Haji Khalifa, Umar Riza Kahhola, Fuad Sezgin from Eastern scholars, Yilmaz Hayriddin, Ahmad Ozel from Turkish researchers, V.V. Bartold, W.B. Hallaq from Western scholars, and Muhammad Sadiq Muhammad Yusuf, Ashirbek Muminov from Uzbek scholars.